Iron Man and Thor. God complex, Part 3 - Abnett, Dan (Iron Man and Thor, 2011)
Thor, God of Thunder and heir to the ancient and mythic heritage of divine power, and Iron Man, an invincible hero and miracle of science and engineering, come together to fight a menace that is both magical and technological.